Central fatigue is greater than peripheral fatigue in people with joint hypermobility syndrome. (October 2019) - To, May; Strutton, Paul H.; Alexander, Caroline M.
Abstract: Purpose: People with Joint Hypermobility Syndrome (JHS) suffer with fatigue. The purpose of this project was to investigate the contribution of central and peripheral fatigue. Methods: Electrical stimulation of the musculocutaneous nerve to biceps brachii, and transcranial magnetic stimulation over the motor cortex supplying biceps brachii were used. Peripheral and central fatigue were assessed during a control, fatiguing and recovery phase protocol. Results: JHS participants perceived greater fatigue during the protocol compared to a control group and did not recover. Central and peripheral fatigue did not occur in the control group. However, the JHS group showed central fatigue. MEP amplitude increased in the JHS group during the fatiguing protocol (p < 0.01) before recovering. Superimposed twitch amplitude increased in the JHS group during the fatiguing protocol and stayed elevated during the recovery phase (p < 0.04). Time to peak (TTP) amplitude of the torque generated by the TMS was longer in the JHS group (p < 0.05). RMS during MVCs decreased during the fatiguing protocol reaching significance during the recovery phase (p < 0.01). Conclusion: JHS participants suffered central but not peripheral fatigue. A modified strength programme to target this is discussed.